A Fantasy and Magical Adsorbent for Heavy Metal Ions Removal: Melamine. (November 2020) - Guo, Jing; Qiu, Hongzhi; Wang, Caiqiong; Hao, Zhihui; Zhang, Chenyu; Peng, Hao
Abstract: Many kinds of research had been done to treat the wastewater containing heavy metal ions in the world. Adsorption technology had attracted much more attention owing to ease of regeneration, simple operation and high-efficiency. Melamine possessed a great surface area especially modified with organic compounds. It showed efficient adsorption efficiency for various valent metal ions ranged from +1 to +6, which exhibited a bright application future for the treatment of wastewater.